Simulation of 6 Elements Aperture Coupled Feed Planar Array Rectangular Microstrip Patch Antenna for CPE WiMAX Application at 3.3 GHz - Yusnita Rahayu; Rezki Ananda Gusma (IAES Indonesia Section, 2014)
In this paper, Simulation of the 6 Elements Aperture Coupled Feed Planar Array Rectangular Microstrip Patch Antenna is designed for CPE WiMAX Application. This Antenna uses Aperture Coupled feed to improve bandwidth. The Proposed antenna is compared to similar design of antenna with Microstrip Line feed, to justify that the proposed antenna produces broader bandwidth. Both of Antennas are designed and simulated by using HFSS simulation software and operated in WiMAX frequency range of 3.3 GHz. The 6 Elements Aperture Coupled Feed antenna gives an impedance bandwidth of 10.53 %, this is broader than the 6 Elements Microstrip Line Feed Antenna which is only has impedance bandwidth of 6.23 %. The maximum gain is obtained 8.4327 dBi at 3.4 GHz. Details of antenna design are given and simulation results are discussed.